2021
DOI: 10.1038/s41598-021-85358-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of wearable sensors to assess compliance of asthmatic children in response to lockdown measures for the COVID-19 epidemic

Abstract: Between March and April 2020, Cyprus and Greece health authorities enforced three escalated levels of public health interventions to control the COVID-19 pandemic. We quantified compliance of 108 asthmatic schoolchildren (53 from Cyprus, 55 from Greece, mean age 9.7 years) from both countries to intervention levels, using wearable sensors to continuously track personal location and physical activity. Changes in ‘fraction time spent at home’ and ‘total steps/day’ were assessed with a mixed-effects model adjusti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 50 publications
4
30
0
Order By: Relevance
“…Heterogeneity in the study types was observed as follows: cross-sectional (n = 9; 53%), longitudinal (n = 4; 24%), retrospective (n = 1; 6%), narrative review (n = 1; 6%) and pilot non-randomized studies (n = 2; 12%). Similar heterogeneity was found in participants too in the included studies: pregnant women [27], elderly [24,26], office workers [21], diabetes [18] and children [25]. All the studies were from high-income countries.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Heterogeneity in the study types was observed as follows: cross-sectional (n = 9; 53%), longitudinal (n = 4; 24%), retrospective (n = 1; 6%), narrative review (n = 1; 6%) and pilot non-randomized studies (n = 2; 12%). Similar heterogeneity was found in participants too in the included studies: pregnant women [27], elderly [24,26], office workers [21], diabetes [18] and children [25]. All the studies were from high-income countries.…”
Section: Resultssupporting
confidence: 60%
“…Seven studies administered smartphone-based physical activity measurement through inbuilt accelerometers from which the captured data were transferred to the cloud server and visualized in smartphone applications [16-19, 21, 24, 31]. Majority of studies (n = 9; 53%) employed wrist bands and wristwatches of multiple technology firms (Apple, Samsung, Xiaomi) and wearable research-based accelerometers [20,23,25,26,[28][29][30]32]. A few studies (n = 4; 24%) reported the psychometrics of the wearables, and lowto-moderate validity was found [21,22,27].…”
Section: Wearables and The Measurement Of Physical And Physiological Variablesmentioning
confidence: 99%
“…Dynamics of trends in wearable sensor using trend analysisThis study also shows that studies on wearable sensor are growing significantly in detection and monitoring technologies. Since wearable sensors can be assumed as biosensors connected to the body, assessing different biological elements, the health care system is one of the essential applications (Chen et al, 2021; Feng et al, 2021;Kouis et al, 2021). In fact, the embedding of wearable sensor systems in health treatment procedures reduces the cost of hospitals' daily expenditures, including patient monitoring and vital sign measurement.…”
mentioning
confidence: 99%
“…Results also show that wearable sensors can be biosensors connected to the body for assessing different biological elements; therefore, the healthcare system is one of the essential applications [ 52 , 90 , 91 ]. In fact, the embedding of wearable sensor systems in health treatment procedures reduces the cost of hospitals’ daily expenditures.…”
Section: Resultsmentioning
confidence: 99%